Archaeal nitrification is a key driver of high nitrous oxide emissions from arctic peatlands. (October 2019) - Siljanen, Henri M.P.; Alves, Ricardo J.E.; Ronkainen, Jussi G.; Lamprecht, Richard E.; Bhattarai, Hem R.; Bagnoud, Alexandre; Marushchak, Maija E.; Martikainen, Pertti J.; Schleper, Christa; Biasi, Christina
Abstract: Bare peat surfaces created by frost action and wind erosion in permafrost peatlands have been shown to emit high amounts of nitrous oxide (N2 O). With global warming, emissions of this highly potent greenhouse gas are expected to increase in Arctic permafrost peatlands. In natural unmanaged soils with low nitrogen deposition, such as Arctic soils, nitrification is the main source of nitrite and nitrate, and thus a key driver of N2 O emissions. Here, we investigated nitrification, ammonia oxidizer populations and N2 O production in vegetated and bare peat soils from four distant Arctic geographic locations. Through a combination of molecular analyses and group-specific inhibitor assays, we show that ammonia oxidation, the first step in nitrification, is mainly performed by ammonia-oxidizing archaea (AOA). All soils from different locations, including bare peat soils with high N2 O emissions, harbored only two AOA phylotypes, including an organism closely related to Ca . Nitrosocosmicus spp. This indicates that high N2 O emissions from these ecosystems are primarily fueled by nitrification mediated by very few archaeal species. To our knowledge, arctic peat soils in this study are the first natural environments where high N2 O emissions have been linked to AOA. Any changes in archaeal nitrification induced by global warming will therefore impact on N2 O emissions from the permafrost peatlands. Highlights: Ammonia-oxidizing archaea (AOA) are driving nitrification in Arctic peat soils which have high N2 O emissions. Arctic peat soils have with only two AOA phylotypes surprisingly low diversity of AOA. AOA are important key species for nitrification in Arctic peat soils.